Strengthening Global Diversity Character P5 Through The Sociodrama Method Of South Sulawesi Folktales - Arni Arni; Khaerun Nisa'a Tasyibu; Firdha Razak (ALENA : Journal of Elementary Education, 2026)
Observations in October 2024 at SDN 8 Pulau Laiya showed that fifth-grade students had difficulty recognizing local cultural identity, tended to imitate irrelevant social media content, and did not understand their own regional culture and stories. They were also less able to explore and appreciate cultural diversity in Pangkep, knowing only their own culture, and showed a tendency to compare and be less accepting of other cultures and beliefs. Stereotypes and ridicule of cultural differences, especially between the Bugis and Makassar tribes, still occur frequently. Participation in joint decision-making is also low, with students tending to be passive and follow the opinions of class leaders or teachers. The values of inclusiveness and social justice are not yet well established. This study aims to apply the *sociodrama* method based on local folklore as a learning strategy to instill the values of global diversity. The approach used is descriptive qualitative with data collection techniques through observation, questionnaires, and interviews. The results show an increase in character traits such as tolerance, empathy, cooperation, and social awareness. Narratives have also proven effective in instilling the values of the Pancasila Student Profile, including responsibility, communication skills, problem solving, and fair leadership.